2003
DOI: 10.1136/heart.89.2.150
|View full text |Cite
|
Sign up to set email alerts
|

NT-proBNP: a new diagnostic screening tool to differentiate between patients with normal and reduced left ventricular systolic function

Abstract: Objective: To evaluate whether measurements of N-terminal pro-brain natriuretic peptide (NT-proBNP) can be used to differentiate patients with normal and reduced left ventricular ejection fraction (LVEF) in an unselected consecutive group of hospital inpatients. Setting: City general hospital, Copenhagen, Denmark. Patients and design: During a 10 month period 2230 admissions to a city general hospital (80% of targeted patients) had an echocardiographic evaluation of left ventricular function, a comprehensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
115
1
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(131 citation statements)
references
References 31 publications
6
115
1
9
Order By: Relevance
“…Sensitivity of NT-proBNP for SLVF in both examinations was high (95.1 and 93.3%, respectively). These high levels of sensitivity, found also in other studies (Emdin et al, 2005;Foote and Pearlman, 2004;Bay et al, 2003), suggest that NT-proBNP may be valid marker for SLVF estimation. Sensitivity of NT-proBNP for DLVF was lower than for SLVF, while specificity in the initial examination was 100%.…”
Section: Specificity Sensitivity and Predictive Value Of Ntprobnp Fosupporting
confidence: 54%
See 2 more Smart Citations
“…Sensitivity of NT-proBNP for SLVF in both examinations was high (95.1 and 93.3%, respectively). These high levels of sensitivity, found also in other studies (Emdin et al, 2005;Foote and Pearlman, 2004;Bay et al, 2003), suggest that NT-proBNP may be valid marker for SLVF estimation. Sensitivity of NT-proBNP for DLVF was lower than for SLVF, while specificity in the initial examination was 100%.…”
Section: Specificity Sensitivity and Predictive Value Of Ntprobnp Fosupporting
confidence: 54%
“…Thus, our subjects were classified into these groups according to their NT-proBNP levels, and there was higher number of patients (> 70.0% of all examinees) in group 2 (levels of NT-proBNP higher than 14.75 pmol/L) as expected, since it was shown in earlier studies that patients with NSTE-ACS have elevated levels of NTproBNP (Sabatine et al, 2002;Lindahl et al, 2005;Jernberg et al, 2004;Heeschen and Hamm, 2004). It was also suggested that the NT-proBNP level increases with the level of symptoms as assessed by New York Heart Association (NYHA) classification and the level of impaired left ventricular dysfunction as assessed by echocardiography (Bay et al, 2003;Pfister et al, 2004;Hess et al, 2005a;Drewniak et al, 2008;Kaski et al, 2010). Numerous studies indicate that levels of NTproBNP in ACS patient can vary between very low and very high (James et al, 2003;Heeschen and Hamm, 2004;Hess et al, 2005a), for example in a study by NT-proBNP, N-Terminal pro-B-type natriuretic peptide; CK, creatine kinase; CK-MB, creatine kinase-mB; cTnT, cardiac troponin T; CRP, C-reactive protein; HF, heart failure; UA, unstable angina; AMI, acute myocardial infarction; LE, lethal event.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Large studies in the general population or in noncardiac patients showed that measuring natriuretic peptides might be an effective screening method for left-ventricular systolic dysfunction (McDonagh et al, 1998;Luchner et al, 2000;Bay et al, 2003). In patients with the suspicion of heart failure several other studies showed natriuretic peptides to be useful indicators for the detection of heart failure (Lerman et al, 1993;Davidson et al, 1996;Cowie et al, 1997;Hammerer-Lercher et al, 2001;Maisel et al, 2002Maisel et al, , 2003.…”
mentioning
confidence: 99%
“…Other patient characteristics that may influence the BNP level, independent of disease, are advancing age, probably reflecting LV subclinical abnormalities (15) and female sex, both of which result in increased BNP level (15,16). Two additional studies have confirmed the correlation of NT pro-BNP with age, but not with sex (17,18). In contrast, obesity is associated with decreased levels of BNP, probably as a result of increased clearance through a receptor contained in adipose tissue (19).…”
mentioning
confidence: 99%